Parental Responsibility for Children's Psychological and Social Development After Divorce in Tondong Tallasa District, Pangkep Regency - Sikra; Agus Muchsin; Ali Rusdi; Hannani; Rahmawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study analyzes "Parents' Responsibility for the Psychological and Social Development of Children After Divorce in Tondong Tallasa District, Pangkep Regency", with the aim of finding outHow is the responsibility of parents towards the psychological and social development of children after divorce in Tondong Tallasa District, Pangkep Regency, What is the impact of psychological and social law on children after divorce in Tondong Tallasa District, Pangkep Regency, and also How is the resolution of parental responsibility towards the psychological and social development of children after divorce in Tondong Tallasa District, Pangkep Regency. The method used in this study is a qualitative method with data collection used, namely data by collecting from the results of observation, documentation, and interviews. The data source is from the Pangkajene Religious Court and documentation from the KUA Tondong Tallasa District, and the research instrument is the researcher himself and assisted by data collection tools, namely observation guide sheets, interview guidelines, data collection techniques are observation, interviews, and documentation; and testing the validity of the research results is the extension of participation, researcher persistence, and triangulation. The results of this study on parental responsibility for the psychological and social development of children after divorce in Tondong Tallasa District, Pangkep Regency explore how parents manage their roles in supporting children who experience major changes in their lives due to divorce. In addition, this study examines the legal impacts that can affect children's psychology and social, including possible shifts in social relationships and the emotional adaptation process faced by children after divorce. Finally, this study offers practical solutions for parents in fulfilling their responsibilities, including positive communication and engagement strategies.